Ex vivo glucocorticoid‐induced secreted proteome approach for discovery of glucocorticoid‐responsive proteins in human serum. Issue 2 (12th March 2021) - Inder, Warrick J.; Mohamed, Ahmed; Keshvari, Sahar; Barclay, Johanna L.; Ruelcke, Jayde E.; Stoll, Thomas; Nolan, Brendan J.; Cesana‐Nigro, Nicole; Hill, Michelle M.
Abstract: Purpose: To identify glucocorticoid‐responsive proteins measurable in human serum that may have clinical utility in therapeutic drug monitoring and the diagnosis of cortisol excess or deficiency. Experimental Design: A phased biomarker discovery strategy was conducted in two cohorts. Secretome from peripheral blood mononuclear cells (PBMC) isolated from six volunteers after ex vivo incubation ± dexamethasone (DEX) 100 ng/mL for 4 h and 24 h was used for candidate discovery and qualification using untargeted proteomics and a custom multiple reaction monitoring mass spectrometry (MRM‐MS) assay, respectively. For validation, five candidates were measured by immunoassay in serum from an independent cohort ( n  = 20), sampled at 1200 h before and after 4 mg oral DEX. Results: The discovery secretome proteomics data generated a shortlist of 45 candidates, with 43 measured in the final MRM‐MS assay. Differential analysis revealed 16 proteins that were significant in at least one of two time points. In the validation cohort, 3/5 serum proteins were DEX‐responsive, two significantly decreased: lysozyme C ( p  < 0.0001) and nucleophosmin‐1 ( p  < 0.01), while high mobility group box 2 significantly increased ( p  < 0.01). Conclusions and Clinical Relevance: Using an ex vivo proteomic approach in PBMC, we have identified circulating glucocorticoid‐responsive proteins which may have potential as serum biomarkers of glucocorticoid activity.